عہد نبویﷺ میں معاشرے کے ثقافتی رجحانات( صحاح ستہ میں وارد اشعار کی روشنی میں): Cultural Trends of Society in the Era of Prophet [S.A.W]: In the light of Poetic verses mentioned in Six Authentic Books of Hadith - Muhammad Saeed -ul-Rehman; Dr. Shah Moheen ud Din Hashmi (Seerat Studies, 2023)
Islam lays stress upon the great values of civilization and culture. The given study shows the signs of Arabic poetry notified in the text of Sihah-e-Sittah (six authentic books of Hadiths). The current study expresses the cultural aspects of Arabic poetry and effects of Prophetic teachings upon the society. There are approximately 100 Hadiths which have Arabic poetry with different topics such as tafseer, Prophethood, doomsday, jihad, happiness, supplications, pedigree, praising of Prophet Muhammad (PBUH) and monotheism as well.